Rapid, selective, and ultrasensitive fluorescence ratiometric detection of sulfide ions using dual-emitting BSA–erbium(iii)-modulated gold–silver bimetallic nanoclusters1. Issue 10 (21st May 2015) - Li, Chun-Mei; Ding, Shou-Nian
<x xml:space="preserve">Abstract</x> Dual-emitting bovine serum albumin–erbium(iii) complex-modulated gold–silver bimetallic nanoclusters (BSA–Er/Au/Ag-NCs) have been synthesized for the first time by a simple one-pot synthesis route.